Opinions of school administrators in high image schools on external pressure groups - Vildan Yılmaz Ortadağ; Soner Polat (Anadolu Üniversitesi Eğitim Fakültesi dergisi)
This research aims to determine the demands of pressure groups towards school administrators working in schools with high image and the behaviors of school administrators towards these demands. The study group consists of 13 school administrators working in the Gebze, İzmit, and Çayırova districts of Kocaeli province in the 2023-2024 academic year. In selecting participants in the study, schools with high images were determined by consulting with district administrators. Interviews were held with 13 school administrators, including nine principals and four deputy principals, from the identified 30 schools. The study group was selected using a purposeful sampling method. In this study, the phenomenology pattern, one of the qualitative research methods, was used. Data were collected through face-to-face interviews by preparing a semi-structured interview form. The data obtained was analyzed using the content analysis method. Codes, categories, and themes were reached through the answers given by the participants. Data analysis determined that the primary demands made by external pressure groups to the administrators of schools with a high image include attempts to enroll students outside the registration area and teacher selection. Other demands made to schools include student enrollment through donations despite no quota, transfer procedures, enrollment of students in need of special education, class changes, ensuring academic success, individual attention from teachers to students, student participation in social activities, renewal of school equipment, presence of security at the school gate, cleanliness of the school, presence of a sports hall in the school, earlier opening and later closing times for the school, and provision of school transportation. Requests mostly come from parents. It has been observed that parents put pressure on administrators through political authorities and public officials to realize their demands. It has been determined that school administrators accepted the legally appropriate requests and rejected the others.